Sequential versus nonsequential two-photon double ionization of the D2 molecule at 38 eV (2009)
ABSTRACT: A simple theoretical model is used to interpret recent experimental results for two-photon double ionization (DI) of D2 at 38 eV. We show that the measured kinetic energy distribution associated with emission of two protons can be interpreted as a sum of two processes: a sequential and an instantaneous absorption of the two incident photons. These processes lead to peaks in di erent regions of the spaectrum.